Preparation and regeneration method of bimetallic Fe-Cu-BTC desulfurizer

Through the preparation and regeneration technology of bimetallic Fe–Cu–BTC materials, the problems of low sulfur capacity and difficulty in regeneration of MOFs adsorbents are solved, efficient H2S removal and good regeneration effects are achieved, and desulfurization activity and regeneration performance are significantly improved.

CN116173924BActive Publication Date: 2025-01-14TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310269999.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-18
Publication Date
2025-01-14
Estimated Expiration
2043-03-18

AI Technical Summary

Technical Problem

The existing MOFs adsorbents have low sulfur capacity and difficulty in regeneration during the H2S desulfurization process, which limits their industrial applications and has low catalytic oxidation activity, making it difficult to effectively remove H2S.

Method used

Bimetallic Fe–Cu–BTC materials are prepared by hydrothermal reaction, and the Lewis acidic site of variable valence metal iron achieves dual functions of adsorption and catalysis. The regeneration method after vulcanization includes heating and hot air treatment to generate CuS, Fe2S3 and other sulfurization. Regeneration of the object.

Benefits of technology

Efficient H2S removal was achieved, with the removal amount reaching 113-123 mg S/g under normal temperature conditions and good regeneration effect. The removal amount reached 68 mg S/g under normal temperature water vapor conditions and 43.7 mg S/g under dry conditions, which was significantly Improves the activity and regeneration properties of the desulfurizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116173924B_ABST
    Figure CN116173924B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a bimetallic Fe-Cu-BTC desulfurizer, which is prepared by a one-step hydrothermal method using ferric nitrate, copper nitrate and trimesic acid as raw materials. The molar doping amount of the desulfurizer ferric nitrate is 10-20% of that of copper nitrate. The bimetallic Fe-Cu-BTC material prepared by the invention can be used as a fine desulfurizer to achieve simultaneous adsorption and catalysis of H2S under normal temperature conditions, which not only solves the problem of poor adsorption or catalytic oxidation activity of MOF materials at normal temperature, but also provides a solution to the difficulty of regeneration of MOFs materials after adsorption. The desulfurizer prepared by the invention is suitable for fine removal of H2S-containing gas in industrial applications such as natural gas refining, petroleum refining, coke oven gas purification and sewage treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation and regeneration method of a bimetallic Fe-Cu-BTC desulfurizer. Background Art

[0002] With the proposal of dual carbon goals and increasingly stringent environmental regulations, low-carbon, clean and efficient utilization of fossil energy is the direction of future development. 2 S) is a highly toxic, foul-smelling gas that is commonly found in various fossil energy sources, such as natural gas, coal-to-gas and liquefied petroleum gas. 2 The presence of sulfur gas will corrode equipment pipelines, poison catalysts in downstream processes, and be oxidized to produce sulfur dioxide when discharged into the atmosphere, leading to acid rain and haze. 2 The efficient removal of S plays a very important role in pollution control and environmental protection in industrial processes.

[0003] Adsorption desulfurization is a process in which solid adsorbent reacts with H 2 S interacts with each other to aggregate and deposit, thus achieving separation. Due to its simple operation process, green environmental protection, low energy consumption and high desulfurization accuracy, it has long attracted attention. Metal-organic framework materials (MOFs), as a new type of porous material, have abundant active sites and ultra-large specific surface area, and are widely studied in the field of adsorption desulfurization. However, the MOFs adsorbents reported so far face the problems of low sulfur capacity and difficult regeneration, which greatly limits their practical industrial applications.

[0004] Catalytic oxidation is H 2 The process of converting sulfur into elemental sulfur by catalytic reaction on a catalyst has almost no side reactions at room temperature and has high selectivity, so it has received widespread attention in recent years. Common catalysts are mainly metal oxides and carbon materials. However, they are affected by the pore structure and active components, which makes them inherently less active and usually requires further modification to improve their activity. MOFs materials can combine the advantages of both, that is, they have abundant active sites that can catalyze conversion and have a developed pore structure to store the generated elemental sulfur. However, due to the problem of difficulty in dissociating hydrogen sulfide, its activity is still low.

[0005] The coupling of adsorption desulfurization and catalytic oxidation desulfurization can improve the activity of a single function in the reaction. The adsorption process is beneficial to H 2 The dissociation of S is beneficial to promote its conversion at the catalytic active sites. In addition, the elemental sulfur generated by the catalytic oxidation reaction can be deposited in the pores, which can disperse the sulfides generated by the adsorption reaction, and is expected to achieve partial regeneration of the desulfurizer, making up for the difficulty of regeneration of adsorption desulfurization.

[0006] In addition, MOFs desulfurizers have the technical problem of poor regeneration performance or almost no regeneration ability. Summary of the invention

[0007] The first technical problem to be solved by the present invention is to provide a method for preparing a bimetallic Fe-Cu-BTC desulfurizer. The preparation method is simple and efficient. The bimetallic Fe-Cu-BTC desulfurizer prepared by the method can be used as a room temperature H 2 Compared with traditional MOFs adsorbents, S-fine desulfurizer utilizes the substitution of variable-valence metal iron to achieve a bimetallic Lewis acid site, which enables it to have both adsorption and catalytic dual-functional desulfurization effects.

[0008] The second technical problem to be solved by the present invention is to provide a regeneration method for the above-mentioned bimetallic Fe-Cu-BTC desulfurizer after sulfidation, which method has simple steps, convenient operation and good regeneration effect.

[0009] In order to solve the above technical problems, the present invention provides a method for preparing a bimetallic Fe-Cu-BTC material, which is prepared by using ferric nitrate, copper nitrate and trimesic acid as raw materials in a hydrothermal reaction, and the specific steps are as follows:

[0010] (1) adding trimesic acid to a mixed solution of N,N-dimethylformamide and anhydrous ethanol, and stirring at room temperature to obtain a solution A;

[0011] (2) adding a soluble iron salt and a soluble copper salt to deionized water, and stirring at room temperature to obtain a solution B, wherein the soluble iron salt is a mixture of one or both of ferric nitrate and ferric chloride, and the soluble copper salt is a mixture of one or both of copper nitrate and copper chloride;

[0012] (3) Solution A and Solution B are mixed, stirred for 10 min to obtain a mixed solution, and placed in a high-pressure reactor with a polytetrafluoroethylene liner, and placed in a forced air drying oven at 70 to 120° C. to react for 20 to 28 h;

[0013] (4) After cooling naturally to room temperature, the reaction product was taken out, placed on a circulating water vacuum pump device for suction filtration, and washed twice with N,N-dimethylformamide and anhydrous ethanol respectively, and then immersed in dichloromethane, and the dichloromethane was replaced once a day for two days;

[0014] (5) The product was filtered again and dried in a forced air drying oven at 45 °C for 4 h to obtain a Fe-Cu-BTC desulfurizer.

[0015] Preferably, the soluble iron salt is ferric nitrate, the soluble copper salt is copper nitrate, and the molar doping amount of the ferric nitrate is 10-20% of that of the copper nitrate.

[0016] In order to solve the above second technical problem, the present invention provides a bimetallic Fe-Cu-BTC desulfurizer prepared by a preparation method of a bimetallic Fe-Cu-BTC desulfurizer, and a regeneration method of a sulfided sample thereof comprises the following steps:

[0017] Take a sulfide sample and place it on a U-shaped fixed bed reactor. Air is introduced into the sample at a flow rate of 50-200 mL / min, and the temperature is increased to 160°C at a heating rate of 1-2°C / min, and maintained at this temperature for 1-2 hours, followed by natural cooling to obtain a regenerated desulfurizer.

[0018] Beneficial effects of the present invention:

[0019] Compared with traditional MOFs adsorbents, the Fe-Cu-BTC desulfurizer prepared by the present invention has a dual-functional desulfurization effect of adsorption and catalysis by using the substitution of variable-valent metal iron to achieve a bimetallic Lewis acid site. 2+ The sites play a role in adsorption, activation, and H 2 S reaction, while Fe 3+ The sites allow the adsorption of H 2 S is catalytically oxidized to elemental S. The synergy of the two reactions makes the desulfurization effect reach an unprecedented level. 2 The amount of S removed reached 113-123 mg S / g.

[0020] Moreover, the introduction of Fe can also promote the growth of Cu-BTC crystals, the formation of grains and the improvement of pore structure, which makes the desulfurizer prepared by the present invention have a more stable physical structure, which is also one of the characteristics of the present invention.

[0021] Another beneficial effect achieved by the present invention:

[0022] Traditional MOFs reversible adsorption usually relies on weak physical adsorption, which makes H 2 The S adsorption capacity is extremely low, which greatly limits the practical application of MOFs materials. Therefore, the method proposed in the present invention relies on the CuS and Fe generated by the reaction. 2 S 3 At the same time, the catalytically generated elemental S can be stored in the pore structure and maintain the integrity of the MOF structure, thereby well dispersing the generated sulfide. Therefore, the generated elemental S and sulfide can react under hot air conditions to generate SO 2 The desulfurizer can be partially regenerated by the coexistence of elemental S and sulfide. Under normal temperature and water vapor conditions, H 2The amount of S removed reached 68 mg S / g, and could reach 43.7 mg S / g under dry conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD spectra of bimetallic Fe–Cu–BTC with different Fe / Cu ratios.

[0024] Figure 2 SEM images of bimetallic Fe–Cu–BTC with different Fe / Cu ratios.

[0025] Figure 3 N of bimetallic Fe–Cu–BTC with different Fe / Cu ratios 2 Adsorption–desorption isotherms.

[0026] Figure 4 N of bimetallic Fe–Cu–BTC with different Fe / Cu ratios 2 Pore ​​size distribution diagram.

[0027] Figure 5 FTIR spectra of bimetallic Fe–Cu–BTC with different Fe / Cu ratios.

[0028] Figure 6 The penetration curves of bimetallic Fe–Cu–BTC with different Fe / Cu ratios.

[0029] Figure 7 The breakthrough sulfur capacity diagram of the bimetallic Fe–Cu–BTC after regeneration with a Fe / Cu ratio of 20%.

[0030] Figure 8 SEM image of bimetallic Fe–Cu–BTC with a Fe / Cu ratio of 20%. DETAILED DESCRIPTION

[0031] The present invention uses a fixed bed experimental device to test the adsorption and catalytic oxidation performance of the refined desulfurizer of each embodiment and comparative example. The specific operation and process are as follows: Take an appropriate amount of desulfurizer and fill it into a U-shaped reactor with an inner diameter of 6mm, where the sample filling height is 2cm. Before the experiment begins, the sample needs to be activated to remove the impurity molecules in the pores. The specific process uses N 2 Purge at 150-180℃ for 8-12h. Then start the desulfurization test. 2 S and N 2 The mixed gas is introduced into the U-tube reactor, and the gas inlet H is adjusted. 2 S concentration is 600 mg / m 3 , the gas flow rate is 100 mL / min, the reaction temperature is 30°C, and the reaction pressure is normal pressure.

[0032] Record the outlet gas H at different times 2 S concentration. When the outlet gas concentration is 1% of the inlet gas concentration, it is 6 mg / m 3 , regarded as the desulfurizer breakthrough point, corresponding to the breakthrough sulfur capacity Q. The calculation formula is:

[0033]

[0034] Where N represents the gas flow rate, C in and C out Respectively represent the import and export H 2 S concentration, m represents the mass of the desulfurizer.

[0035] Example 1.

[0036] Weigh 1 g of trimesic acid, add it to a mixed solution of 17 mL of N,N-dimethylformamide and 17 mL of anhydrous ethanol, and stir evenly at room temperature to obtain solution A.

[0037] Weigh 0.28 g of ferric nitrate nonahydrate and 1.8 g of copper nitrate trihydrate, add them into 17 mL of deionized water, and stir evenly at room temperature to obtain solution B.

[0038] The above solution A and solution B were mixed, stirred for 10 min to obtain a mixed solution, and placed in a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, and placed in a forced air drying oven at 85° C. for reaction for 24 h.

[0039] After naturally cooling to room temperature, the reaction product was taken out, placed on a circulating water vacuum pump device for filtration, and washed twice with N,N-dimethylformamide and anhydrous ethanol respectively. The product was then immersed in dichloromethane, and the dichloromethane was replaced once a day for two days.

[0040] Subsequently, the product was filtered again and dried in a forced air drying oven at 45°C for 4 h to obtain a Fe–Cu–BTC-10% desulfurizer.

[0041] The Fe–Cu–BTC-10% desulfurizer obtained in this example has a specific surface area of ​​875 m2 / g and a total pore volume of 0.48 cm 3 / g, of which the micropore volume is 0.38cm 3 / g, mesopore volume 0.09cm 3 / g. After testing, the breakthrough sulfur capacity of the desulfurizer was calculated to be 113.3 mg S / g.

[0042] Example 2.

[0043] Weigh 1 g of trimesic acid, add it to a mixed solution of 17 mL of N,N-dimethylformamide and 17 mL of anhydrous ethanol, and stir evenly at room temperature to obtain solution A.

[0044] Weigh 0.41 g of ferric nitrate nonahydrate and 1.7 g of copper nitrate trihydrate, add them into 17 mL of deionized water, and stir evenly at room temperature to obtain solution B.

[0045] The above solution A and solution B were mixed, stirred for 10 min to obtain a mixed solution, and placed in a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, and placed in a forced air drying oven at 85° C. for reaction for 24 h.

[0046] After naturally cooling to room temperature, the reaction product was taken out, placed on a circulating water vacuum pump device for filtration, and washed twice with N,N-dimethylformamide and anhydrous ethanol respectively. The product was then immersed in dichloromethane, and the dichloromethane was replaced once a day for two days.

[0047] Subsequently, the product was filtered again and dried in a forced air drying oven at 45°C for 4 h to obtain a Fe–Cu–BTC-15% desulfurizer.

[0048] The specific surface area of ​​the Fe-Cu-BTC-15% desulfurizer obtained in this example is 951 m 2 / g, total pore volume 0.51cm 3 / g, of which the micropore volume is 0.40cm 3 / g, mesopore volume 0.1cm 3 / g. After testing, the breakthrough sulfur capacity of the desulfurizer was calculated to be 119.3 mg S / g.

[0049] Example 3.

[0050] Weigh 1 g of trimesic acid, add it to a mixed solution of 17 mL of N,N-dimethylformamide and 17 mL of anhydrous ethanol, and stir evenly at room temperature to obtain solution A.

[0051] Weigh 0.54 g of ferric nitrate nonahydrate and 1.6 g of copper nitrate trihydrate, add them into 17 mL of deionized water, and stir evenly at room temperature to obtain solution B.

[0052] The above solution A and solution B were mixed, stirred for 10 min to obtain a mixed solution, and placed in a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, and placed in a forced air drying oven at 85° C. for reaction for 24 h.

[0053] After naturally cooling to room temperature, the reaction product was taken out, placed on a circulating water vacuum pump device for filtration, and washed twice with N,N-dimethylformamide and anhydrous ethanol respectively. The product was then immersed in dichloromethane, and the dichloromethane was replaced once a day for two days.

[0054] Subsequently, the product was filtered again and dried in a forced air drying oven at 45°C for 4 h to obtain a Fe–Cu–BTC-20% desulfurizer.

[0055] The specific surface area of ​​the Fe-Cu-BTC-20% desulfurizer obtained in this embodiment is 1006 m 2 / g, total pore volume 0.54cm 3 / g, of which the micropore volume is 0.37cm 3 / g, mesopore volume 0.17cm 3 / g. After testing, it was calculated that the breakthrough sulfur capacity of the desulfurizer was 122.8mg S / g.

[0056] Will remove H 2 The Fe–Cu–BTC-20%-E waste desulfurizer after S was placed in a U-shaped reactor fixed bed, and air was introduced into the sample at a flow rate of 100 mL / min, and the temperature was raised to 160°C at a heating rate of 1°C / min, and maintained at this temperature for 2 hours. Then the temperature was naturally cooled to obtain the regenerated desulfurizer Fe–Cu–BTC-20%-R. After testing, it was calculated that the breakthrough sulfur capacity of Fe–Cu–BTC-20%-R under water vapor conditions was 68.2 mg S / g, and the breakthrough sulfur capacity under dry conditions was 43.7 mg S / g.

[0057] Comparative example.

[0058] Weigh 1 g of trimesic acid, add it to a mixed solution of 17 mL of N,N-dimethylformamide and 17 mL of anhydrous ethanol, and stir evenly at room temperature to obtain solution A.

[0059] Weigh 2 g of copper nitrate trihydrate and add it to 17 mL of deionized water. Stir evenly at room temperature to obtain solution B.

[0060] The above solution A and solution B were mixed, stirred for 10 min to obtain a mixed solution, and placed in a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, and placed in a forced air drying oven at 85° C. for reaction for 24 h.

[0061] After naturally cooling to room temperature, the reaction product was taken out, placed on a circulating water vacuum pump device for filtration, and washed twice with N,N-dimethylformamide and anhydrous ethanol respectively. The product was then immersed in dichloromethane, and the dichloromethane was replaced once a day for two days.

[0062] Subsequently, the product was filtered again and dried in a forced air drying oven at 45°C for 4 h to obtain the Cu-BTC desulfurizer.

[0063] The specific surface area of ​​the Cu-BTC desulfurizer obtained in this example is 798 m 2 / g, total pore volume 0.40cm3 / g, of which the micropore volume is 0.38cm 3 / g, mesopore volume 0.02cm 3 / g. After testing, the breakthrough sulfur capacity of the desulfurizer was calculated to be 57.4 mg S / g.

[0064] Will remove H 2 The Cu–BTC-E waste desulfurizer after S was placed in a U-shaped reactor fixed bed, and air was introduced into the sample at a flow rate of 100 mL / min, and the temperature was raised to 160°C at a heating rate of 1°C / min, and maintained at this temperature for 2 hours. Then the temperature was naturally cooled to obtain the regenerated desulfurizer Cu–BTC-R. After testing, it was calculated that the breakthrough sulfur capacity of Cu–BTC-R under water vapor conditions was 14.7 mg S / g, and the breakthrough sulfur capacity under dry conditions was 10.2 mg S / g.

[0065] In order to more clearly and intuitively compare the texture parameters and performance of the bimetallic Fe-Cu-BTC desulfurizer prepared by the present invention, they are summarized in Table 1. It can be seen that compared with pure Cu-BTC, the bimetallic Fe-Cu-BTC has a larger specific surface area and pore volume, which indicates that the introduction of iron will improve the physical structure of MOF. At the same time, the penetration sulfur capacity of the desulfurizer has been significantly improved, especially in Example 3, where the activity has been increased by 114% compared with the monometallic Cu-BTC. This is because the bimetallic Fe-Cu-BTC desulfurizer prepared by the present invention has both adsorption and catalytic dual functions to remove H 2 S's ability, Cu 2+ Site and H 2 The strong binding ability of S can promote the adsorption and dissociation of the latter, and react to generate CuS; Fe 3+ The sites can absorb H 2 S is catalytically oxidized to elemental S, and the two work together to significantly increase the sulfur capacity.

[0066] Table 1 Physical structure and performance parameters of desulfurizers in various embodiments and comparative examples

[0067]

[0068] In order to understand the effect of Fe introduction on the crystal structure of Cu-BTC materials, XRD tests were carried out on single metal Cu-BTC and bimetal Fe-Cu-BTC. The results are shown in Figure 2. Figure 1As shown. It can be seen that compared with the single metal Cu-BTC, the XRD peak position of the bimetallic Fe-Cu-BTC has hardly changed, which shows that the introduction of Fe will not affect the crystal structure of Cu-BTC. However, the diffraction peak intensity of the bimetallic Fe-Cu-BTC is significantly higher than that of Cu-BTC, which shows that the introduction of Fe can promote the crystallization of the crystal and improve the stability of the structure.

[0069] Furthermore, the morphology of the prepared single metal Cu-BTC and bimetal Fe-Cu-BTC was observed by scanning electron microscopy. Figure 2 As shown. The morphology of the single metal Cu-BTC is a "double pyramid" type octahedral structure, the crystal surface is smooth, and the grain size is about ~10μm. After the introduction of Fe, the morphology of Fe-Cu-BTC is still octahedral, but the difference is that the grain size is significantly increased and more regular. The results of scanning electron microscopy show that the introduction of Fe promotes the growth of crystals, which is consistent with the results of XRD.

[0070] Nitrogen adsorption was used to further analyze the pores of the prepared desulfurizer. The nitrogen adsorption-desorption isotherms were as follows: Figure 3 As shown. The single metal Cu-BTC is a typical type I isotherm, indicating that its structure is mainly composed of micropores. The bimetallic Fe-Cu-BTC not only has a type I isotherm, but also a type IV isotherm, with an obvious hysteresis loop between the relative pressures of 0.42-0.99, indicating that the introduction of Fe will promote the formation of mesopores. Figure 4 The pore size distribution shows that the distribution range of mesopores is 2-30 nm; moreover, after the introduction of Fe, the nitrogen adsorption amount is significantly higher than that of single metal Cu-BTC, indicating that its specific surface area has been improved with the introduction of Fe.

[0071] The infrared spectra of Cu-BTC and bimetallic Fe-Cu-BTC are shown in Figure 5 As shown in the figure, it can be seen that there are several typical adsorption peaks of single metal Cu-BTC: at 1374 and 1446 cm -1 The absorption peak at 1642cm is attributed to the symmetrical vibration peak of the carboxyl group of the organic ligand; -1 The absorption peak at 1300-700cm -1 In the region of BTC, several absorption peaks related to the plane vibration of the ligand BTC can be seen. After the introduction of the Fe component, the infrared absorption peak of the bimetallic Fe–Cu–BTC did not change at all, indicating that the chemical bonds and functional groups of Fe–Cu–BTC remain the same as those of Cu–BTC and have not changed.

[0072] The desulfurization activity of the prepared single metal Cu-BTC and bimetal Fe-Cu-BTC was tested by fixed bed. The breakthrough curves and breakthrough sulfur capacity results are shown in Figure 6 and Figure 7 As shown in the figure. The penetration time of Cu-BTC is 275 min, and the corresponding penetration sulfur capacity is 57.4 mg S / g. After the introduction of Fe, the penetration time is significantly improved, and the penetration time of Fe-Cu-BTC-20% is increased to 600 min, and the penetration sulfur capacity is also 122.8 mg S / g. This fully shows that the bimetallic Fe-Cu-BTC is very effective for H 2 The removal of S is very effective. This is because the introduction of Fe improves the structure of Cu-BTC, not only enhancing the crystallinity, but also promoting the growth of grain size, improving the pore structure and specific surface area. More importantly, the introduction of Fe promotes the 2 The process of S catalysis to elemental S leads to an unprecedented improvement in desulfurization activity through the synergistic adsorption reaction of Cu sites.

[0073] Furthermore, we heat-treated the samples in air to achieve their regenerative properties. Figure 7 As shown. It can be seen that the performance of the single metal Cu-BTC is significantly reduced after regeneration, and the sulfur capacity under water vapor conditions and dry conditions is 14.7 and 10.2 mg S / g, respectively. Although the performance of the bimetallic Fe-Cu-BTC-20% is also significantly reduced after regeneration, it still maintains good regeneration activity, and the sulfur capacity under water vapor conditions and dry conditions is 68.2 and 43.7 mg S / g, respectively. The regeneration performance is even better than that of the fresh sample Cu-BTC. The main reason for the excellent regeneration performance is that the introduction of Fe makes H 2 S is catalytically oxidized to elemental S, which is favorable for conversion to SO in an air atmosphere. 2 On the other hand, the generated elemental S will be stored in the pore structure of MOF, playing a certain supporting role, which makes H 2 The sulfides formed by the reaction of S with metal centers can be better dispersed, which can be achieved by Figure 8 The SEM image of Fe–Cu–BTC-20%-E after desulfurization is shown, which is also beneficial to the regeneration of sulfides. Therefore, Fe–Cu–BTC-20% has excellent desulfurization activity and regeneration activity.

Claims

1. Application of a bimetallic Fe-Cu-BTC desulfurizer in fine desulfurization of hydrogen sulfide at room temperature, characterized in that: The bimetallic Fe-Cu-BTC desulfurizer is prepared by hydrothermal reaction using ferric nitrate, copper nitrate and trimesic acid as raw materials, and the specific steps are as follows: (1) adding trimesic acid to a mixed solution of N, N-dimethylformamide and anhydrous ethanol, and stirring at room temperature to obtain a solution A; (2) adding a soluble iron salt and a soluble copper salt to deionized water, and stirring at room temperature to obtain a solution B, wherein the soluble iron salt is ferric nitrate, and the soluble copper salt is copper nitrate, and the molar doping amount of the ferric nitrate is 15-20% of that of the copper nitrate; (3) Solution A and solution B were mixed, stirred for 10 min to obtain a mixed solution, and placed in a high-pressure reactor with a polytetrafluoroethylene liner, and then placed in a forced air drying oven at 70-120°C for reaction for 20-28 h; (4) After cooling naturally to room temperature, take out the reaction product, place it on a circulating water vacuum pump device for filtration, and wash it twice with N, N-dimethylformamide and anhydrous ethanol respectively. Then, soak the product in dichloromethane, and change the dichloromethane once a day for two days; (5) The product was filtered again and dried in a forced air drying oven at 45 °C for 4 h to obtain a Fe–Cu–BTC desulfurizer.

2. The use of a bimetallic Fe-Cu-BTC desulfurizer in room temperature hydrogen sulfide fine desulfurization according to claim 1, characterized in that: The regeneration of the bimetallic Fe–Cu–BTC desulfurizer includes the following steps: The Fe–Cu–BTC waste desulfurizer after H2S removal was placed in a U-shaped fixed bed reactor, and air was introduced into the sample at a flow rate of 50~200 mL / min. The temperature was increased to 160°C at a heating rate of 1~2°C / min and maintained at this temperature for 1~2h. The temperature was then naturally cooled to obtain the regenerated desulfurizer.

Citation Information

Patent Citations

  • Bimetal MOFs material for CO2 capture and preparation method and application thereof

    CN112979977A